Early experiences with robot-assisted prosthetic breast reconstruction - Ahn, Sung Jae; Song, Seung Yong; Park, Hyung Seok; Park, Se Ho; Lew, Dae Hyun; Roh, Tai Suk; Lee, Dong Won (Archives of plastic surgery, 2019)
Robotic surgery facilitates surgical procedures by employing flexible arms with multiple degrees of freedom and providing high-quality 3-dimensional imaging. Robot-assisted nipplesparing mastectomy with immediate reconstruction is currently performed to avoid breast scars. Four patients with invasive ductal carcinoma underwent robot-assisted nipple-sparing mastectomy and immediate robot-assisted expander insertion. Through a 6-cm incision along the anterior axillary line, sentinel lymph node biopsy and nipple-sparing mastectomy were performed by oncologic surgeons. The pectoralis major muscle was elevated, an acellular dermal matrix (ADM) sling was created with robotic assistance, and an expander was inserted into the subpectoral, sub-ADM pocket. No patients had major complications such as hematoma, seroma, infection, capsular contracture, or nipple-areolar necrosis. The mean operation time for expander insertion was 1 hour and 20 minutes, and it became shorter with more experience. The first patient completed 2-stage prosthetic reconstruction and was highly satisfied with the unnoticeable scar and symmetric reconstruction. We describe several cases of immediate robot-assisted prosthetic breast reconstruction. This procedure is a feasible surgical option for patients who want to conceal surgical scars.